KINEMATICSOF THEPLANAR QUADRILATERAL MECHANISM - Florian Ion PETRESCU; Victoria PETRESCU (Fiabilitate şi Durabilitate)
This paper presents an original method to determine the kinematic parameters at the linkedquadrilateral mechanism. It is starting with a trigonometric method, which has the advantage to determine veryquickly the position angles. The velocities can be determined faster using a geometric method. This method isdeveloped and for the accelerations determinations. The (proposed) geometric method, determines first thekinematic parameters of the internal couple (B) and then the rotation angles with their derivatives. Secondary,the paper presents the determination of the efficiency of this mechanism. Determines and dynamic coefficient, D.With this one proposes two yields; the mechanical efficiency and the dynamic efficiency.